An Overview of Thyroid Cancer Genetics and Inheritance - Diana Navas-Carrillo; Esteban Orenes-Pinero (Global Journal of Cancer Therapy - Peertechz Publications, 2015)
Thyroid cancer (TC) is the most common endocrine malignancy and its incidence hasbeen increasing sharply since the mid-1990s [1]. TC is a general term that comprises two main groups of neoplasias, depending on the cell type affected by the malignant transformation. 1) Carcinomas originating from the follicular epithelium, referred to as nonmedullary thyroid cancer (NMTC) representing more than 95% of all TC; and 2) carcinomas originating from the parafollicular thyroid C cells, referred to as medullary thyroid cancer (MTC) accounting less than 5% of all TC. Although MTC accounts only for 5% of all the thyroid cancers, it is responsible forabout 15% of all the deaths related to thyroid cancer [2]. Familial medullary thyroid carcinoma (FMTC) encompasses about 25% of all the medullary thyroid carcinomas, appearing as part of a rare inherited syndrome called multiple endocrine neoplasia 2(MEN2) or as isolated FMTC. These familial forms have in common germline gain-of function mutations in the RET proto-oncogene, located on chromosome 10q1 1.2 [2]. Almost all patients with a germline RET mutation develop c-cell hyperplasia or MTC during their lifetime. Today, about 98% of all the mutations responsible for FMTC areknown.